The Flow of Social Environmental Determinants of Disabilities on Lepers in Tuban City - Rockmawati, Dliyau; Aris Santjaka; Lagiono; Nur Hilal; Khomsatun; Hari Rudjianto Indro Wardono; Ririh Yudhastuti; Soedjajadi; Lilis Sulistyorini; R. Azizah; Khuliyah Candraning Diyanah; Chatarina Umbul Wahyuni; Hari Basuki Notobroto; Nasichatus Shofa (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Leprosy is a neglected tropical disease considered rare in most areas despite having a relatively high incidence in some countries. Objective: Analyze the flow of determinants of the social environment that can affect the occurrence of disability in lepers and their impacts. Method: Research using a qualitative approach. The research was conducted in Tuban Regency, East Java Province. The informant selection technique uses a purposeful sampling technique. Data analysis uses triangulation techniques. Results: The frequency of leprosy in Tuban Regency tended to decrease from 2014-2019. Leprosy distribution occurred in 18 sub-districts; Lepers were found every month in 2019 with various characteristics of lepers that cause the emergence of leprosy and disability in leprosy. The total number of informants in this study was seven informants. Determinants of disability in lepers include informant characteristics and social environment, including knowledge, contact history, family support, self-confidence, and impact. Conclusion: In this study, the social environment that most impact the occurrence of disability in lepers is the informant knowledge factor. Informant knowledge is influenced by education, a large network of friends, and technological literacy. Education will show the type of informant work, and the type of work will determine the income of the informant; income determines economic status. Economic status contributes to food intake, medication seeking, and the home's physical condition. The duration of leprosy treatment will affect the worsening of the disability if good self-care is not carried out and always use PPE when doing activities.